2008
DOI: 10.2528/pierm08010702
|View full text |Cite
|
Sign up to set email alerts
|

Neural Frequency Sweeper for Accelerating S-Parameters Calculation of Planar Microwave Structures

Abstract: Abstract-This paper presents a new frequency-sweep approach for the efficient calculation of S-parameters of planar microwave structures. The approach is based on approximating the frequency dependence of the real and imaginary parts of the S-parameters using neural networks. Due to its superior performance, radial basis functions neural network (RBF-NN) is adopted. A limited number of frequency samples are used to train the RBF-NN. Then, the trained RBF-NN is capable of providing a smooth frequency response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The same study confirmed SmHMGR as the target of statins, as their effect was reversed upon treatment with 2 m m mevalonate . In vivo, only moderate activities were found ,. Lovastatin ( 66 ) reduced worm burden in mice infected with adult S. mansoni by 30 % (oral administration of 400 mg kg −1 day −1 for five days) .…”
Section: Anthelmintic Drug Therapymentioning
confidence: 57%
See 1 more Smart Citation
“…The same study confirmed SmHMGR as the target of statins, as their effect was reversed upon treatment with 2 m m mevalonate . In vivo, only moderate activities were found ,. Lovastatin ( 66 ) reduced worm burden in mice infected with adult S. mansoni by 30 % (oral administration of 400 mg kg −1 day −1 for five days) .…”
Section: Anthelmintic Drug Therapymentioning
confidence: 57%
“…Lovastatin ( 66 ) reduced worm burden in mice infected with adult S. mansoni by 30 % (oral administration of 400 mg kg −1 day −1 for five days) . Furthermore, 67 reduced the worm burden in hamsters infected with adult S. haematobium by 46 %, but a longer duration of treatment was needed (intragastrical application of 0.9 mg kg −1 for 49 days) . It is feasible that a higher dosage would give better results in vivo, especially because the lethal dose of 66 is greater than 5 g kg −1 …”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%
“…In regions III and I, m decreases to a lower value of ≤ 0⋅2, and ductility is less. Region I has not been observed by many investigators (Soliman 1995;Yousefiani and Mohammed 1998;Duong and Mohamed 2000) when using superpure superplastic materials and region III was attributed to the operation of dislocation creep (Abo-Elhkier and Soliman 2006). It has been established recently that region I does not represent a genuine change in the rate controlling mechanism, but rather arises from operation of a threshold process due to segregation of impurity atoms on the grain boundaries (Chaudhury and Mohamed 1988;Mohamed 1988).…”
Section: Introductionmentioning
confidence: 95%
“…The deformation behaviour of superplastic materials have been divided into three deformation regions (Soliman 1994;Mohammed 2002), designated as I, II and III at low, intermediate and high strain rates, respectively. In region II, the material is characterized by high strain rate sensitivity index, m ~ 0⋅5, and the activation energy is very close to that of grain boundary diffusion, and maximum ductility is usually observed.…”
Section: Introductionmentioning
confidence: 99%